DINAMIKA ADVOKASI PERUBAHAN IKLIM OLEH YAYASAN KONSERVASI WAY SEPUTIH DI LAMPUNG TIMUR - Surya Artini, Kadek Ayu; Hermawan, Dedy; Prihantika, Ita (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
East Lampung Regency, known as one of the main food-producing regions, has been designated as a priority area in the agricultural sector. In this context, the Way Seputih Conservation Foundation (YKWS) has undertaken advocacy efforts related to climate change issues in the region. This study aims to examine the advocacy process carried out by YKWS and to identify various factors that hinder its implementation. A qualitative approach with descriptive analysis was used, employing Rahardian’s (2020) theory as the main analytical framework. The findings indicate that YKWS's advocacy efforts have not been fully optimal. This is due to limited community and media involvement, an overly theoretical approach, insufficient use of digital media, and the absence of evaluation and post-advocacy consolidation. These findings underscore the importance of collaboration among various stakeholders to support the sustainability of the advocacy process in order to produce tangible and lasting change.